Command in war: : Operational conduct of war and political control of military operations - Valdés Guía, Pedro (Dia-noesis: A Journal of Philosophy, 2024)
At a time when advances in technology are accelerating the trend towards blurring the boundaries between the different levels of conduct of military operations, this work provides a comprehensive analysis, with a historical perspective, of the subject of command in war. The book addresses the issue of the command of military operations during armed conflict, in order to elucidate whether its "operational occurrence" is a mere continuation of politics, when it brings its most serious means into play, or whether, on the contrary, it introduces a new logic into the political process, which could not be managed according to the parameters of instrumental reason. Aware that the hierarchical-instrumental subjection constitutes the "normal paradigm" of Western political-military relations for the conduct of war, the novelty of this book lies in the judgement of this paradigm, not from the political logic that, obviously, would like to express itself with a docile and versatile grammar, but from the intrinsic demands of its operational occurrence.